2007
DOI: 10.1021/jp075834j
|View full text |Cite
|
Sign up to set email alerts
|

Osmotic Pressure beyond Concentration Restrictions

Abstract: Osmosis is a fundamental physical process that involves the transit of solvent molecules across a membrane separating two liquid solutions. Osmosis plays a role in many biological processes such as fluid exchange in animal cells (Cell Biochem. Biophys. 2005, 42, 277-345;1 J. Periodontol. 2007, 78, 757-7632) and water transport in plants. It is also involved in many technological applications such as drug delivery systems (Crit. Rev. Ther. Drug. 2004, 21, 477-520;3 J. Micro-Electromech. Syst. 2004, 13, 75-824) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 28 publications
2
39
0
Order By: Relevance
“…When we transfer the GUV into a hypotonic solution where the glucose concentration is C out (< C in 0 ) (i.e., DC 0 ¼ C in 0 À C out ) (where the units of all the concentrations are mol/m 3 (mM)), P is applied to the GUV due to the difference in the chemical potential of water inside and outside of the GUV. It is reported that when the concentrations, C, of sucrose and glucose are low (i.e., C < 100 mM) the linearity between P and C holds, and thus, the ideal equation (van't Hoff's law) for P can be used (31,32). We also measured osmolarity (mOsm/L) of sucrose and glucose solutions of <98 mM and obtained the linear relationship between the osmolarity and the molar concentration (Fig.…”
Section: Measurement Of P-induced Volume Changes Of Dopc-guvsmentioning
confidence: 86%
“…When we transfer the GUV into a hypotonic solution where the glucose concentration is C out (< C in 0 ) (i.e., DC 0 ¼ C in 0 À C out ) (where the units of all the concentrations are mol/m 3 (mM)), P is applied to the GUV due to the difference in the chemical potential of water inside and outside of the GUV. It is reported that when the concentrations, C, of sucrose and glucose are low (i.e., C < 100 mM) the linearity between P and C holds, and thus, the ideal equation (van't Hoff's law) for P can be used (31,32). We also measured osmolarity (mOsm/L) of sucrose and glucose solutions of <98 mM and obtained the linear relationship between the osmolarity and the molar concentration (Fig.…”
Section: Measurement Of P-induced Volume Changes Of Dopc-guvsmentioning
confidence: 86%
“…However, below it is shown that, for example, for the membrane used in [12] and a 1 M (1:1) electrolyte solution, F can be as large as ca. 180.…”
Section: Theorymentioning
confidence: 99%
“…In [12], the osmotic pressure in concentrated solutions of sucrose was studied by using a specially designed membrane osmometer. To avoid the deformation and eventual rupture of the membrane, the latter was supported by a porous metal disk.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the T i and T e values may be affected not only by osmotic pressure but also by hydrophilicity of osmotic agents. According to Van't Hoff equation (Grattoni et al, 2007), the same amount of mannitol created the lowest osmotic pressure in tablet resulted in the longest Te. The same amount of lactose created relatively high osmotic pressure, but the rate of water hydration of tablet core with lactose as the osmotic agent was lower than that of tablet core with mannitol as the osmotic agent.…”
Section: Development Of Cro Osmotic Pump Tabletsmentioning
confidence: 99%